Influence Of Motivation And Emotional Intelligence On Employee Performance With Organizational Citizenship Behavior As A Mediating Variable At Bni Bank Offices Bengkulu - Betarina , Nurmalia; Widodo, Slamet; Nugroho, Sigit (The Manager Review, 2023)
Abstract.  This research aims to examine the influence of motivation and emotional intelligence on employee performance which is mediated by Organizational Citizenship Behavior. Research was conducted using a survey method with a special quantitative research approach at the BNI KC Bengkulu bank to test the existence of motivation, emotional intelligence, Organizational Citizenship Behavior which influence employee performance. The research sampling method used in this research is the census. Sampling method in which all members of the population are the unit of analysis. The unit of analysis in this research is an individual who is an employee of BNI KC Bengkulu bank. This research uses the PLS test tool. The research results reveal that motivation has no significant effect on Organizational Citizenship Behavior. Emotional intelligence influences organizational citizenship behavior. Organizational citizenship behavior has a significant effect on employee performance. Motivation does not have a significant effect on employee performance. Emotional intelligence has a significant effect on employee performance. In the mediation relationship, Organizational Citizenship Behavior is known to be unable to mediate the relationship between employee motivation and performance. Furthermore, Organizational Citizenship Behavior can significantly mediate the relationship between emotional intelligence and employee performance. Keywords: motivation, emotional intelligent, organizational citizenship behavior, employee performance